Concept of Wealth Circulation in Islam According to the Perspective of Islamic Economics - Ferdi Prayoga; Kiki Razroma Yantika; Eli Febriani; Nurvina Hidayati; Iiz Izmuddin (Universitas 17 Agustus 1945 Semarang, 2025)
The concept of circulation in Islam is a holistic approach that considers various aspects of life, including economic, social, and spiritual dimensions. It emphasizes the importance of harmony and harmony in society, focusing on principles of amal, social justice, and ethical conduct. This approach encourages individuals to interact and interact with others, fostering harmony and unity in all aspects of life. circulation also encourages individuals to be innovative in addressing challenges, fostering innovation, and promoting cooperation. It also encourages a collaborative approach to social issues, fostering a sense of community and shared goals. By promoting collaboration and dialogue, society can adopt a more positive perspective, encourage innovation, and foster creative solutions. Circulation is a key aspect of the Islamic economic system, which aims to create a stable and harmonious society. It encourages individuals to contribute actively to the development of society and contribute to the development of the future. The system also encourages individuals to share their experiences and unique experiences, fostering a sense of community and fostering innovation.